Analisis Kinerja BUMDes Makmur Sejahtera Desa Pongangan Kecamatan Manyar - Farichah, Faidatul; Cahyadi, Nur (Universitas Muhammadiyah Gresik, 2024)
Background – This research was conducted at the Makmur Sejahtera Village-Owned Enterprise (BUMDes) of Pongangan Village, Manyar District. BUMDes Makmur Sejahtera has realized community welfare in terms of what the needs of the community are through the business units it runs, and BUMDes Makmur Sejahtera has been responsive in finding what the needs of the community are. Objective – The purpose of this study was to determine how the performance of the Village-Owned Enterprises (BUMDes) Makmur Sejahtera Pongangan village Manyar sub-district and to find out what factors support the performance of the Village-Owned Enterprises (BUMDes) Makmur Sejahtera Pongangan village Manyar sub-district. Design / Methodology / Approach – This research uses a qualitative descriptive method. The samples used were the BUMDes director, BUMDes treasurer, and Pongangan villagers. The data collection method used was to survey respondents through interviews with informants. Findings – In the management of BUMDes Makmur Sejahtera has implemented the principles well, namely the productivity of BUMDes Makmur Sejahtera creates many business unit programs that run smoothly, the quality of service is able to provide satisfaction to BUMDes users by establishing business units in accordance with user needs, the responsibility of administrators and officers is committed and carries out their respective duties and authorities well. The accountability of BUMDes Makmur Sejahtera is said to be good because it routinely conducts monthly to annual reporting. As well as the support of several factors in encouraging BUMDes performance, namely government support, resources and leadership. Research Implication – The impact of the BUMDes research results for future management studies can contribute to the development of management theory, especially in the context of local economic development and economic independence of village communities and can help develop a more effective management system. Limitations – The limitations of this research are that the performance portrayed is more on the qualitative data side but what is poured does not add and display the performance from year to year of the Village-Owned Enterprises (BUMDes) Makmur Sejahtera Pongangan Village, Manyar District.